2010
DOI: 10.1103/physrevlett.105.023201
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniversal Efimov Atom-Dimer Resonances in a Three-Component Mixture ofLi6

Abstract: We observed an enhanced atom-dimer loss due to the existence of Efimov states in a three-component mixture of 6Li atoms. We measured the magnetic-field dependence of the atom-dimer loss in the mixture of atoms in state |1> and dimers formed in states |2> and |3>, and found two peaks corresponding to the degeneracy points of the energy levels of |23> dimers and the ground and first excited Efimov trimers. We found that the locations of these peaks disagree with universal theory predictions, in a way that cannot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
167
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(176 citation statements)
references
References 28 publications
(41 reference statements)
9
167
0
Order By: Relevance
“…In particular, we observed the temperature dependence of the RF spectrum, and found a resonance shift with temperature. Operating at lower temperature to eliminate this shift, we found that the measured energies significantly deviate from those of Ref.[16] and the previous predictions [13]. Refining the model to fit these measurements, we obtain a non-monotonic energy dependence of the three-body parameter Λ.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…In particular, we observed the temperature dependence of the RF spectrum, and found a resonance shift with temperature. Operating at lower temperature to eliminate this shift, we found that the measured energies significantly deviate from those of Ref.[16] and the previous predictions [13]. Refining the model to fit these measurements, we obtain a non-monotonic energy dependence of the three-body parameter Λ.…”
mentioning
confidence: 57%
“…[16] and the previous predictions [13]. Refining the model to fit these measurements, we obtain a non-monotonic energy dependence of the three-body parameter Λ.…”
Section: Recently T Lompe Etalmentioning
confidence: 88%
See 2 more Smart Citations
“…The scattering length has a pole at resonance, corresponding to a two-body bound state exactly at threshold. Signatures of Efimov states were first observed in an ultracold gas of cesium atoms [7] and have since been found in many other systems, including other bosonic gases [8][9][10][11][12][13], three-component fermionic spin mixtures [14][15][16][17], and mixtures of atomic species [18][19][20][21]. Moreover, extensions of the Efimov scenario to universal states of larger clusters [22][23][24] have been demonstrated in experiments [9,25,26], highlighting the general nature of universal few-body physics.…”
Section: Introductionmentioning
confidence: 94%